Job titles and education requirements of registered nurses in primary care: An international document analysis. (November 2021) - Barrett, Crystal; Mathews, Maria; Poitras, Marie-Eve; Norful, Allison A.; Martin-Misener, Ruth; Tranmer, Joan; Ryan, Dana; Lukewich, Julia
Abstract: Background: Registered nurses have increasingly taken on new, integrated roles across a variety of health care settings, thus leading to a lack of clarity among titles used to identify registered nurses. Protected titles, such as "registered nurse, " identify regulated professionals, whereas informal job titles identify nurses by their education or practice area. The variation in education requirements of registered nurses and the inconsistency in titles used to identify registered nurses in primary care internationally limits the ability to compare research findings and policies across countries. There is also minimal documentation on the education requirements specific to registered nurses in primary care. Objectives: This study aims to (a) outline protected titles and education requirements for registered nurses; and (b) identify job titles and education requirements specific to registered nurses in primary care internationally. Methods: A modified document analysis with key informant consultations was employed. Organization for Economic Co-operation and Development and key partner countries were considered for inclusion ( n =42). Online searches were performed using keywords (e.g. nurse, title, nursing education) to identify data focused on protected titles and education requirements of registered nurses, and job titles and education requirements of registered nurses in primary care. Data were extracted from online sources and verified for accuracy and completeness by key informants, identified for each country through online searches or professional networks. Results: Out of the 42 eligible countries, 24 countries were included in the final analysis. Five countries were excluded for their lack of available documents in English or French and 13 countries were excluded due to an inability to verify data with key informants. The findings show that "registered nurse" is the most common protected title internationally. Other protected titles include "general nurse" and "nurse." Many unofficial job titles for registered nurses in primary care were identified, including "primary care nurse, " "general practice nurse, " and "community nurse." Twelve countries had no specific job title for registered nurses in primary care. Consistently, there was no mandatory education required for registered nurses to practice in primary care. However, many countries had primary care-specific programs available for nurses to gain knowledge in this area. Conclusions: This study confirms that job titles used to identify registered nurses in primary care vary considerably across countries. A unified understanding of international nomenclature for this role can support and facilitate future research, education, and policy development to recognize and optimize primary care nursing by improving access and quality of care for individuals, families, and communities. Tweetable abstract: Globally, job titles of RNs in primary care vary considerably and there are no formal primary care education requirements to practice.